2013
DOI: 10.1111/ctr.12194
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of tonsillectomy for recurrent IgA nephropathy after kidney transplantation

Abstract: N. Outcome of tonsillectomy for recurrent IgA nephropathy after kidney transplantation.Abstract: Since 2007, we have performed tonsillectomies for patients with recurrent immunoglobulin A nephropathy (IgAN) after kidney transplantation. Seven patients with primary IgAN showed biopsyproven recurrent IgAN after living-donor kidney transplantation. They had persistent proteinuria or hematuria for an average of 40.3 months, and tonsillectomy was performed, on average, 75.6 months after kidney transplantation. In s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…The urinary findings were improved in all patients after tonsillectomy, including a histologically severe case, for a mean period of 13.5 months [15]. Furthermore, Koshino after tonsillectomy over a mean observation period of 48.4 months [16]. In the current study, patients with tonsillectomy group exhibited improved urinary findings, whereas proteinuria increased significantly in the no tonsillectomy group.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The urinary findings were improved in all patients after tonsillectomy, including a histologically severe case, for a mean period of 13.5 months [15]. Furthermore, Koshino after tonsillectomy over a mean observation period of 48.4 months [16]. In the current study, patients with tonsillectomy group exhibited improved urinary findings, whereas proteinuria increased significantly in the no tonsillectomy group.…”
Section: Discussionsupporting
confidence: 52%
“…It is also important to confirm any changes pathologically using protocol graft biopsies. However, several previous studies [14][15][16]20] did not perform long-term evaluations using protocol graft biopsies. We can also evaluate rejection according to the Banff classification and aggravation of the IgAN process for long-term observation about 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…In renal allografts, histological recurrence has been reported in 50–60% of patients by 5 years . Since the recurrence of IgA nephropathy is regarded as a significant cause of graft dysfunction and failure in kidney transplantation, some approaches to the treatment of recurrent IgA nephropathy have been proposed …”
Section: Iga Nephropathymentioning
confidence: 99%
“…No specific treatment for recurrent IgA nephropathy is currently available. However, three studies from Japan showed that a tonsillectomy improved clinical and histological damage in patients with IgA recurring after kidney transplantation . Hotta et al .…”
Section: Iga Nephropathymentioning
confidence: 99%
See 1 more Smart Citation